PERCEIVED STRESS, COPING RESOURCES, AND LIFE SATISFACTION AMONG U. S. AND MEXICAN COLLEGE STUDENTS: A CROSS-CULTURAL STUDY - Matheny, Kenneth B.; Roque-Tovar, Bernardo Enrique; Curlette, William L. (Anales de Psicología / Annals of Psychology, 2008)
This article presents a cross-cultural study of the perceived stress, coping resources, and life satisfaction of college students in Mexico and the United States. Two-hundred-six Mexican college students (41 males and 165 females) and 241 U.S. college students (69 males and 172 females) completed the Perceived Stress Scale, the Coping Resources Inventory for Stress, and the Satisfaction with Life Scale. The analysis of the results was based on a transactional stress model, and it was intended to assess the extent to which perceived stress and coping resources predict life satisfaction. In addition, a description of the cross-cultural and male-female differences is presented. Finally, the authors discuss the appropriateness of the transactional stress model and the use of the three instruments for both Mexican and U.S. students.